Politically Engaged Leisure: The Political Participation of Young People in Contemporary Britain beyond the Serious Leisure Model - Sarah Pickard (Angles)
This article discusses leisure in contemporary Britain pertaining to the political participation of young people in relation to the concepts of ‘serious leisure’ and ‘politically engaged leisure.’ Leisure is a fundamental component of a young person’s individual and collective identities, and some young people discover an interest in politics during their transition to adulthood. Research on the sociological concept of Serious Leisure Perspective (SLP) (Stebbins, 1982) has been carried out regarding many different activities, but it has rarely been considered apropos young people or indeed political activities. This article examines whether the Serious Leisure Perspective can be applied to traditional and innovative forms of political participation carried out by British youth in the twenty-first century and to what extent politically engaged leisure might be a more fitting term. By adopting a cross-disciplinary approach, the article identifies gaps in the current body of work on leisure and aims to add to academic understanding of leisure by pushing the boundaries of the existing conceptualisations of it. The article illustrates that is it possible to conceptualise political participation as a leisure activity and that the Serious Leisure Perspective could be used to describe it. The article goes on to suggest a new concept politically engaged leisure could be a useful way to describe political participation of politically committed young people in contemporary Britain.